2019
DOI: 10.2478/cjf-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Administration of Ethanol and Methanol Extracts of Withania somnifera Root Stimulates Innate Immunity, Physiological Parameters and Growth in Nile Tilapia Oreochromis niloticus

Abstract: Efficacy of ethanol and methanol extracts of medicinal herb Withania somnifera roots was evaluated in Nile tilapia Oreochromis niloticus on immunostimulation and growth. Withania roots were extracted with water, ethanol, methanol, methylene chloride, hexane, successive methanol. Phenol, flavonoid content and antiradical activity of all the extracts were measured. Ethanol extract showed the highest phenol, flavonoid content and antiradical activity followed by methanol extract. Subsequently, Nile tilapia (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Considering that their results were obtained after 55 days of feeding on a supplemented diet, it may be explained as a physiological adaptation to the supplemented diet. The current study results coordinate with Mukherjee et al [55] who detected an elevation in the plasma levels of total protein and total immunoglobulin of Nile tilapia by dietary addition of W. somnifera root extracts.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Considering that their results were obtained after 55 days of feeding on a supplemented diet, it may be explained as a physiological adaptation to the supplemented diet. The current study results coordinate with Mukherjee et al [55] who detected an elevation in the plasma levels of total protein and total immunoglobulin of Nile tilapia by dietary addition of W. somnifera root extracts.…”
Section: Discussionsupporting
confidence: 91%
“…Pratheepa and Sukumaran [79] demonstrated that the increased lysozyme activity could be because of increasing the blood neutrophils and monocytes of fish fed diet fortified with plant extract compared to that found in the control diet. The results of the present study are coordinated with Mukherjee et al [55] who reported an increase in the lysozyme activity in Nile tilapia fed on a diet fortified with W. somnifera root extract. Furthermore, myeloperoxidase (MPO) is a neutrophil released enzyme that is an essential constituent of protection against pathogens [80] and has a vital function for the innate immune response [81].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further, the hypothesized mechanisms of action necessitate comprehensive analysis either by searching for sex gene expression profiles at the transcriptomic level or changes in the sex steroid levels (Capel & Tanaka, 2013; Ross & Capel, 2005), to validate the specific role/s of plant extracts on the tilapia sex differentiation pathway. This would facilitate the designing of a standard utilization protocol including: extraction procedure for bioactive ingredients of interest, extraction solvents that result in highly purified concentrations, administration approaches, and subsequently optimal doses levels of plant extracts (Dhanani et al, 2017; Mukherjee, Ghosal, Moniruzzaman, De, & Chakraborty, 2019).…”
Section: Limitations To the Utilization Of Plant Extracts And Future ...mentioning
confidence: 99%
“…However, there is a growing concern about the application and misuse of antibiotics in the aquaculture industry, as they are transforming the bacteria into resistant variety by transferring resistant genes to the naïve bacteria, which are not exposed to antibiotics (Kraemer et al, 2019). Furthermore, the treatment of the fish with antibiotics gives rise to drug residues, besides having a negative impact on the environment (Mukherjee et al, 2019). Currently many laws and regulations have been implemented to eliminate/minimize the indiscriminate use of antibiotics in the livestock industry to stop the onset of bacterial resistance.…”
Section: Introductionmentioning
confidence: 99%